Co-Electrolysis CFY-Stack Operation and Integration for Carbon Capture and Utilization. (10th July 2019) - Kusnezoff, Mihails; Megel, Stefan; Rix, Christopher; Adam, Paul; Reichelt, Erik; Herz, Gregor; Jahn, Matthias; Trofimenko, Nikolai; Michaelis, Alexander
Abstract : The successful operation of CFY-stack with electrolyte supported cells with Ni/GDC electrode has been demonstrated in electrolysis and co-electrolysis mode at 75-85% gas conversion to provide reliable data for performance and degradation estimation. The difference of stack performance between electrolysis and co-electrolysis modes was <2%. The power consumption in steam and co-electrolysis operation was very similar and depends mainly on Nernst voltage of H2 O/H2 /CO2 /CO containing gas composition. Gas conversion has only minor effect on power consumption over a wide operation window. SOE stack integration into carbon capture and utilization (CCU) unit for production of waxes using Fischer-Tropsch synthesis has been considered on system design level applying realistic efficiencies for internal heat utilization (heat losses). Non-converted syngas and short-chained by-products are recycled to the stack inlet and used for recovery. It has been shown that at T≥800°C a methane content of 7.5 mol-% in the feed gas is fully converted in the stack under co-electrolysis operating conditions.